A 90-liter stackable baffled microbial fuel cell for brewery wastewater treatment based on energy self-sufficient mode. (November 2015) - Dong, Yue; Qu, Youpeng; He, Weihua; Du, Yue; Liu, Jia; Han, Xiaoyu; Feng, Yujie
Highlights: A 90 L baffled MFC stacked with 5 easily-stackable modules was developed. The system was easy to build, extend, and maintain. Long-term performance of the system was investigated. The system was operated in an energy self-sufficient manner. Abstract: A 90-liter stackable pilot microbial fuel cell was designed and proved to be capable for brewery wastewater treatment and simultaneous electricity harvested. The system was stacked by 5 easily-stackable modules, and operated in an energy self-sufficient manner for more than 6 months. Tests were conducted under two different influent strengths (diluted wastewater, stage 1; raw wastewater, stage 2). The COD, SS removal efficiencies were 84.7% and 81.7% at stage 1, 87.6% and 86.3% at stage 2. The system produced enough energy (0.056 kWh/m 3 at stage 1, 0.097 kWh/m 3 at stage 2) to power the pumping system (0.027 kWh/m 3 at both stages), net electrical energy of 0.021 kWh/m 3 and 0.034 kWh/m 3 were harvested. These results show that this pilot-scale system could be used to effectively treat real wastewater with zero energy input.